Habitus of Interreligious Harmony in a Central Java Village - Muhsin, Ilyya; Achmad Maimun; Sukron Ma’mun (Millah: Journal of Religious Studies, 2024)
The diversity present in Nalen is a blessing, as it fosters cohesion in social, cultural, and religious ties, in contrast to the various conflicts that often arise from such differences. This cohesion resulted from the formation of a habitus of peace. This study aimed to answer the question of how the habitus of peace is cultivated in Nalen, a small village in Central Java. Data were systematically collected through in-depth interviews with prominent figures and community members in Nalen, complemented by observations. The subsequent analysis of the data employed Bourdieu’s theoretical framework, which delves into the intricacies of habitus development within the Nalen community. This analysis scrutinizes various forms of capital, with a particular emphasis on social and cultural capital, substantively contributing to the fortification of the habitus. This study finds that the habitus of interreligious harmony can manifest organically, devoid of external coercion, showcasing the community’s robust autonomy in the formative process. Additionally, the objective and subjective structures of society, alongside historical factors, emerge as foundational elements that influence the trajectory of habitus formation. Ultimately, habitus is cultivated within the collective consciousness of the community and is sustained by the diverse capital resources at their disposal.